Language Change and Morphological Processes in Contemporary Chinese: The Case of 健康码 (Health QR Code) - Yun Xiao; Yi Ren (Languages, 2023)
The Chinese language has witnessed remarkable changes in the past several decades, marked by a rapid rise of new words, frequent innovation of pseudo-affixes, and a notable increase in word length. By analyzing the creation, spread, and expansion of the new word 健康码 Jiankang-ma “health QR code”, this study sheds light on how language change takes place and how nonce formation is brought into being. Following the explosion of COVID-19 in China, 健康码 Jiankang-ma “health QR code” was created and promoted by the local and central governments and subsequently generated a large XX-码 XX-ma “XX-code” word family through various morphological processes, such as abbreviation, clipping, derivation, and analogy, where -码 -ma “-code” has acquired some new meaning distinct from its original form as a bound root. Linguistically, 健康码 Jiankang-ma “health QR code” is a three-morpheme word in a 2 + 1 length pattern, which phonologically consists of a single super foot that makes the expression catchy and appealing. The highly productive AB-C internal structure makes -码 -ma “-code”, although not yet a fully grammaticalized affix, a strong pseudo-suffix that has high morphological productivity with a fixed suffix positioning. Given the high frequency of the lexical 码 ma “code” in contemporary Chinese language use, the pseudo-suffix -码 -ma “-code” may, however, not completely replace it in the long run, as principles of grammaticalization theories predict. Instead, it is likely that both the lexical 码ma “code” and the pseudo-suffix -码 -ma “-code” will coexist side by side along split pathways.